A Long Journey through Organic Chemistry – Celebrating Cesare Gennari's 70th Birthday. Issue 44 (22nd November 2022) - Pignataro, Luca; Piarulli, Umberto
Abstract : Cesare Gennari has contributed to many research areas in organic chemistry. On the occasion of his 70th birthday, his friends, colleagues and former students contributed to a special collection which covers his main fields of interest.